Episode-of-Care Costs for Revision Total Joint Arthroplasties by Decadal Age Groups - Christopher Fang; Nicholas Pagani; Matthew Gordon; Carl T. Talmo; David A. Mattingly; Eric L. Smith (Geriatrics, 2021)
The demand for revision total joint arthroplasties (rTJAs) is expected to increase as the age of the population continues to rise. Accurate cost data regarding hospital expenses for differing age groups are needed to deliver optimal care within value-based healthcare (VBHC) models. The aim of this study was to compare the total in-hospital costs by decadal groups following rTJA and to determine the primary drivers of the costs for these procedures. Time-driven activity-based costing (TDABC) was used to capture granular hospital costs. A total of 551 rTJAs were included in the study, with 294 sexagenarians, 198 septuagenarians, and 59 octogenarians and older. Sexagenarians had a lower ASA classification (2.3 vs. 2.4 and 2.7; p < 0.0001) and were more often privately insured (66.7% vs. 24.2% and 33.9%; p < 0.0001) as compared to septuagenarians and octogenarians and older, respectively. Sexagenarians were discharged to home at a higher rate (85.3% vs. 68.3% and 34.3%; p < 0.0001), experienced a longer operating room (OR) time (199.8 min vs. 189.7 min and 172.3 min; p = 0.0195), and had a differing overall hospital length of stay (2.8 days vs. 2.7 days and 3.6 days; p = 0.0086) compared to septuagenarians and octogenarians and older, respectively. Sexagenarians had 7% and 23% less expensive personnel costs from post-anesthesia care unit (PACU) to discharge (p < 0.0001), and 1% and 24% more expensive implant costs (p = 0.077) compared to septuagenarians and octogenarians and older, respectively. Sexagenarians had a lower total in-hospital cost for rTJAs by 0.9% compared to septuagenarians but 12% more expensive total in-hospital costs compared to octogenarians and older (p = 0.185). Multivariate linear regression showed that the implant cost (0.88389; p < 0.0001), OR time (0.12140; p < 0.0001), personnel cost from PACU through to discharge (0.11472; p = 0.0007), and rTHAs (−0.03058; p < 0.0001) to be the strongest associations with overall costs. Focusing on the implant costs and OR times to reduce costs for all age groups for rTJAs is important to provide cost-effective VBHC.